MENINGKATKAN KESADARAN MASYARAKAT TERHADAP PERLINDUNGAN LINGKUNGAN KHUSUSNYA DALAM PERMASALAHAN SAMPAH DI MANIK MARAJA KEC. SIDAMANIK TAHUN 2023 - Khairuddin Tambusai; Dian Reka Bayu; Muhammad Hasby; Dedy Damhuri (STKIP Subang, 2023)
Manik Maraja Village is well-known for its natural beauty and diverse natural resources. However, the village faces a serious problem in waste management, which has resulted in negative impacts on the environment and the quality of life for its residents. Garbage trucks from the district government no longer serve the village adequately, and unfair fees have burdened the residents. Some residents have resorted to managing their waste in ways that are not always environmentally friendly. Effective waste management in this village requires cooperation between the government and the community. This involves education, motivation, and training to enhance awareness and behavior of the community in waste management. The 3R paradigm (reduce, reuse, recycle) becomes a crucial approach in building this awareness. This research examines the potential for waste management in Manik Maraja Village through interviews with local stakeholders. The results indicate the need for more effective and fair solutions in waste management, as well as closer cooperation between the government and the community. Through collective efforts, it is hoped that the village can create a cleaner, healthier, and more sustainable environment.